UNCONVENTIONAL REPLIES: A SPECIAL TYPE OF PHRASEME AND A PAREMIOLOGICAL GENRE - Meterc, Matej; Pallay, Jozef (Proverbium - Yearbook, 2019)
The article investigates unconventional replies and their tar-get statements using various examples from English and five Slavic languages (Slovak, Slovene, Czech, Polish and Russian) and a survey conducted among over 400 Slovene and Slovak students. This paremiological genre – a type of phraseological replies – has received little attention in worldwide research to date. We begin by formulating our own definition. Frequent mechanisms for establishing the link between a target statement and an unconventional reply are presented. Two un-conventional replies from English used in internet memes are analysed along with their equivalents in Slavic languages. The initial results of sociolinguistic research we conducted on 20 Slovene and 20 Slovak unconventional replies are presented, with a focus on how respondents interpret dialogues with unconventional replies. A number of new Slo-vene and Slovak unconventional replies and their variants were collect-ed in the framework of this research, and will need to be analysed in the near future. The conclusion of the article outlines aspects that offer potential for further research on this special type of phraseme and paremiological genre.